2018
DOI: 10.11648/j.bsi.20180302.13
|View full text |Cite
|
Sign up to set email alerts
|

Women’s Autonomy and Reproductive Healthcare-Seeking Behavior in Bangladesh: Further Analysis of the 2014 Bangladesh Demographic and Health Survey

Abstract: Women's autonomy or empowerment is an important issue to achieve targets for the Sustainable Development Goals (SDGs) of Bangladesh. There are several indicators to measure the women empowerment. Health seeking information is one of the most important indicators in this view. This study aims at identifying women's maternal and child health-care seeking in relation to women empowerment in Bangladesh. Bangladesh Demographic and Health Survey (BDHS) 2014 data was used for the study. A total of 1875 women of repro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…During the initial literature search, we found that there were very few studies discussing women's empowerment–related issues in FRH control in Bangladesh. 17 , 38 , 45 , 48 , 49 , 50 , 52 , 53 , 54 , 57 Most of these studies were cross-sectional in nature, and we did not find any review-based studies on this topic. As a first initiative to address all these issues, we reviewed several Bangladesh-based articles from different time periods to provide a more comprehensive understanding of the relationship between women's empowerment and fertility and reproductive behavior.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…During the initial literature search, we found that there were very few studies discussing women's empowerment–related issues in FRH control in Bangladesh. 17 , 38 , 45 , 48 , 49 , 50 , 52 , 53 , 54 , 57 Most of these studies were cross-sectional in nature, and we did not find any review-based studies on this topic. As a first initiative to address all these issues, we reviewed several Bangladesh-based articles from different time periods to provide a more comprehensive understanding of the relationship between women's empowerment and fertility and reproductive behavior.…”
Section: Discussionmentioning
confidence: 94%
“…Respondents’ employment status and wealth index were not truly reflective of their employment situation at the time of each birth. Afroja et al, 49 2018 Women's education, wealth index, decision maker for using contraception, partner's education, women's working status, beating justified if wife goes out without telling husband, neglects the children, argues with husband, refuses to have sex with husband, burns the food. 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Likewise, evidence from LMIC shows that women empowerment is associated with healthcare-seeking behaviours, the use of contraceptives, household decision-making, employment status, and freedom of movement [18]. In Bangladesh, a similar association was reflected between women's autonomy and healthcare service uptake [13,19]. As most women in Bangladesh are submissive to their partners' requests, this influences their sexual and reproductive health [20].…”
Section: Plos Onementioning
confidence: 99%